Resistance test of avian salmonella strains in antibacterial drugs - IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ) P.; GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ) I. (Journal of the Hellenic Veterinary Medical Society, 2018)
In the present paper in vitro resistance of 241 salmonella isolates to 9 antibacterial drugs was studied. Salmonella strains were isolated from various avian species during the period 1990-1994. The resistance of these isolates was determined by using the Kirbi Bauer disc diffusion method. Resistance to Oxytetracycline, furazolidone and trimethoprim ranged from 6 to 50% and the highest percentage (50%) was noted to Oxytetracycline. Resistance to spectinomycin reached the highest levels (56-80%). Similar results were noted by using amoxicillin, to which resistance was relateively lower ( — 50%) with a slight decrease to 15% concerning the year 1992 isolates. Resistance to enrofloxaxin and flumequin was at 25% approximately, only for strains isolated during 1991 and 1992. All remaining isolates were sensitive. Low resistance (11%) declining to 3% during the last year of our investigation was noted when neomycin was used. Finally, resistance to chloramphenicol remained below 10%.